Single crystal alpha-si3n4, and preparation method and application thereof

CN116623281BActive Publication Date: 2026-10-27QIANWAN INST OF CNITECH +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310378617.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-11
Publication Date
2026-10-27
Estimated Expiration
2043-04-11

AI Technical Summary

Technical Problem

但这种方法往往需要较高的温度,增加了能耗

Benefits of technology

[0028](1)本发明采用改进简化的气-固方法,在不使用气体和催化剂的条件下,利用电子束辐照镀有氮化硼薄膜的硅衬底实现了单晶α-Si3N4的生长。该制备方法简单易行,原料易得,节能且对环境无污染。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116623281B_ABST
    Figure CN116623281B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of single crystal alpha-Si3N4, which is prepared by irradiating a silicon substrate plated with a boron nitride film under vacuum conditions by using an electron beam. The application also discloses the single crystal alpha-Si3N4 prepared by the preparation method. The single crystal alpha-Si3N4 has a shape of flower, pine tree, fern leaf or needle. The needle-shaped single crystal alpha-Si3N4 has emission peaks at 540 nm and 633 nm under excitation light at 325 nm. The needle-shaped single crystal alpha-Si3N4 is prepared by irradiating a silicon substrate plated with a 2-3 mu m thick boron nitride film under an irradiation voltage of 78-85 keV and an irradiation beam current of 18-25 mA for 90-120 s. The single crystal alpha-Si3N4 is prepared without using gas and catalyst, the preparation method is simple and easy to implement, raw materials are easy to obtain, energy is saved, the environment is not polluted, and the obtained needle-shaped single crystal alpha-Si3N4 has photoluminescence performance, and has a good application prospect in micro-nano photoelectronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanomaterial preparation technology, specifically to a single-crystal α-Si3N4 and its preparation method and application. Background Technology

[0002] Silicon nitride (Si3N4) is a broadband (5.3 eV) semiconductor. Highly doped Si3N4 exhibits electrical and optical properties similar to III-N compounds (such as GaN and AlN), making it widely used for growing quantum structures to obtain blue lasers. Furthermore, Si3N4 possesses excellent properties such as high mechanical strength, high thermal stability, and high chemical stability, making it an important structural ceramic material. These superior properties are closely related to its crystal structure. One-dimensional Si3N4 nanomaterials, in particular, exhibit many novel properties. For example, the flexural strength and elastic modulus (up to 570 GPa) of Si3N4 nanocrystals are significantly higher than those of bulk materials, making them crucial for applications in nanoelectronic and photonic devices.

[0003] In recent years, researchers have focused on preparing various Si3N4 nanostructures, such as nanowires, nanorods, and nanoribbons. Based on the growth mechanisms of Si3N4 (VLS mechanism, VS mechanism, SLS mechanism, and SLGS mechanism), researchers have proposed several methods for preparing Si3N4 nanostructures.

[0004] Patent CN 109585264 B discloses a flowable chemical vapor deposition method for silicon nitride thin films. This method uses cyclosilanes with a ring-shaped molecular structure as precursors, which are deposited onto a substrate in a periodic "deposition-curing" cycle with nitrogen-containing compounds to form a flowable silicon nitride thin film until the trenches of the substrate are filled. This invention achieves silicon nitride thin films at temperatures only 700–900°C. However, due to the interactions between gases and environmental influences, it is generally difficult to precisely control the formation of one-dimensional silicon nitride crystals.

[0005] The invention patent with authorization announcement number CN 113122925 B discloses a silicon nitride single crystal, its preparation method, and its application. It mainly involves growing Si3N4 crystals by annealing SiC and graphene at a high temperature of 1200–1500℃ under a flowing gaseous nitrogen source. However, due to the use of a carbothermic reduction method in the preparation process, the introduction of a reducing agent may lead to product impurities.

[0006] Patent CN 101550600 B discloses a method for preparing high-purity, high-density single-crystal silicon nitride nanoarrays. This method uses a metal as a catalyst and employs a pyrolysis of organic precursors to synthesize silicon nitride nanoarrays on a substrate coated with a metal catalyst. The pyrolysis of organic precursors can be used to design the size of the silicon nitride product to improve the performance of silicon nitride nanomaterials. However, most polymer precursors are liquid at room temperature, typically requiring an additional solidification process, which increases the number of synthesis steps.

[0007] Compared to the various methods for synthesizing silicon nitride mentioned above, the direct nitriding method has the advantages of simplicity and low equipment requirements. Patent application CN 110357051 A discloses a method for preparing single-crystal α-phase silicon nitride nanowhiskers, which synthesizes single-crystal α-Si3N4 nanowhiskers by directly nitriding silicon powder with nitrogen-containing gas without using any catalyst. However, this method often requires high temperatures, increasing energy consumption.

[0008] Given the limitations of the existing technologies, it is particularly important to find a simple, easy-to-implement, readily available, energy-saving, and environmentally friendly method for preparing single-crystal α-Si3N4. Summary of the Invention

[0009] To address the aforementioned problems, this invention provides a method for preparing single-crystal α-Si3N4. This invention utilizes electron beam irradiation to prepare single-crystal α-Si3N4 on a silicon substrate coated with a boron nitride thin film. The preparation method is simple and easy to implement, uses readily available raw materials, and is environmentally friendly.

[0010] A method for preparing single-crystal α-Si3N4 involves irradiating a silicon substrate coated with a boron nitride thin film under vacuum conditions.

[0011] This invention utilizes electron beam irradiation of a silicon substrate coated with a boron nitride thin film to perform nitridation synthesis in a high-vacuum environment with extremely low oxygen partial pressure, thus preparing single-crystal α-Si3N4. This electron beam irradiation method is a novel processing technology and process that ionizes and excites various material molecules through the interaction of high-energy electrons with matter, thereby initiating chemical reactions to improve material properties or generate new materials. This method not only makes the reaction easier but is also highly energy-efficient.

[0012] Preferably, the vacuum condition is 3 to 5 × 10⁻⁶. -4 Pa.

[0013] Preferably, the electron beam irradiation conditions are as follows: the silicon substrate coated with boron nitride film is placed in the crucible of the electron beam evaporation equipment, and the silicon substrate coated with boron nitride film is irradiated for 10 to 120 seconds under the conditions of irradiation voltage of 74 to 85 keV and irradiation beam current of 15 to 25 mA. After the irradiation is completed, the high voltage power supply is turned off and the crucible is cooled instantly.

[0014] Preferably, the silicon substrate coated with a boron nitride thin film is prepared by the following method:

[0015] (1) The silicon substrate containing the oxide layer was immersed in piranha solution for 12-24 hours, and then ultrasonically cleaned with deionized water, anhydrous ethanol and acetone respectively, and then blown clean with nitrogen gun to obtain the cleaned silicon substrate.

[0016] (2) The cleaned silicon substrate is placed in the magnetron sputtering chamber, and an RF power supply is used with hexagonal boron nitride as the target material, at a back vacuum of 1 to 5 × 10⁻⁶. -4 In an environment of Pa, nitrogen and argon are introduced, with a flow rate ratio of nitrogen to argon of 10–40:40. The gas pressure is adjusted to 0.6–1.5 Pa. The power for sputtering boron nitride thin film is 100–180 W. After evaporation for 3–4 hours, an amorphous thin film with a thickness of 1–3 μm coated with boron nitride is obtained.

[0017] Preferably, in step (1), the oxide layer thickness of the silicon substrate containing the oxide layer is 280-300 nm; the piranha solution is prepared by concentrated sulfuric acid and hydrogen peroxide, and the volume ratio of concentrated sulfuric acid to hydrogen peroxide is 7:3.

[0018] Preferably, in step (2), the purity of the hexagonal boron nitride is 99.99%, and the purity of the nitrogen and argon is 99.9999%.

[0019] The formation of single-crystal α-Si3N4 nanostructures is controlled by composite substrate growth and a VS growth mechanism. When an electron beam rapidly impacts the sample surface, the enormous kinetic energy is converted into thermal energy, causing the sample to melt rapidly. During rapid heating, amorphous boron nitride decomposes into B(g) and N*(g) (highly reactive), while silicon oxide reacts with silicon to generate active SiO(g). Subsequently, SiO(g) and N*(g) recombine to rapidly form silicon nitride molecules. Due to the large temperature difference between the irradiated and unirradiated areas, many Si3N4 nuclei tend to form at the edges of the electron beam. These Si3N4 nuclei are energy-favorable and provide stable sites for the adhesion of other Si3N4 molecules. When irradiation ends, the entire sample cools down abruptly within tens of seconds, slowing the diffusion rate of solute atoms to the solid surface. Silicon nitride crystals preferentially grow slowly at their edges and corners, resulting in single crystals of various morphologies.

[0020] Preferably, the single-crystal α-Si3N4 has a flower-like, pine-like, fern-like, or needle-like shape. The shape of these single crystals is related to the irradiation voltage, irradiation beam current, irradiation duration, and the thickness of boron nitride in the composite substrate.

[0021] Preferably, when the boron nitride film thickness is 2-3 μm, the irradiation voltage is 78-85 keV, the irradiation beam current is 18-25 mA, and the irradiation time is 90-120 s, the single crystal α-Si3N4 obtained is needle-shaped.

[0022] Preferably, the needle-shaped single-crystal α-Si3N4 has a growth length of up to 15 μm and emission peaks at 540 nm and 633 nm under 325 nm excitation light.

[0023] Needle-shaped single-crystal silicon nitride belongs to a one-dimensional nanostructure, and its intrinsic structure contains four defect types: Si-Si bonds, N-N bonds, and two types of Si-N dangling bonds. Si-Si bonds form bonding σ orbitals near the valence band and antibonding σ* orbitals near the conduction band. These two states form an optical band edge at 4.6 eV. The Si dangling bond between N3 and Si (called the K-center) forms a state near the intermediate gap, while the N dangling bond between Si2 and N (called the N-center) forms two defect states near the conduction and valence bands, respectively. and These point defects involve an unpaired electron positioned on a two-coordinated N atom (Si2=N·) and a three-coordinated Si atom (N3≡Si·), which leads to different states.

[0024] The stimulated emission peak of the needle-like single-crystal α-Si3N4 of this invention is attributed to the recombination of the intrinsic conduction band edge with the Si dangling bond N3≡Si·. Furthermore, the numerous peaks around 633 nm are caused by the recombination between the two N dangling bonds, i.e., the intrinsic conduction band edge and... Between and state and Reorganization between states.

[0025] This invention also provides a single-crystal α-Si3N4 prepared by the aforementioned method. This single-crystal α-Si3N4 exhibits photoluminescence properties and variable photoelectronic performance, and has potential application value in optical fields such as photodetectors.

[0026] This invention also provides the application of the aforementioned single-crystal α-Si3N4 in micro / nano optoelectronic devices. The needle-shaped single-crystal α-Si3N4 prepared by this invention exhibits certain photoluminescence properties and shows great promise for application in micro / nano optoelectronic devices.

[0027] Compared with the prior art, the present invention has at least the following beneficial effects:

[0028] (1) This invention employs an improved and simplified gas-solid method to achieve the growth of single-crystal α-Si3N4 by electron beam irradiation of a silicon substrate coated with a boron nitride thin film without the use of gases or catalysts. This preparation method is simple and easy to implement, uses readily available raw materials, is energy-saving, and is environmentally friendly.

[0029] (2) The morphology of the single-crystal α-Si3N4 prepared by the method of the present invention has a certain influence on its optical properties. The prepared needle-shaped single-crystal α-Si3N4 has emission peaks at 540nm and 633nm under 325nm ultraviolet light excitation, and has potential application prospects in optical fields such as photodetectors. Attached Figure Description

[0030] Figure 1 SEM image of single-crystal α-Si3N4 prepared in Example 1;

[0031] Figure 2 SEM image of single-crystal α-Si3N4 prepared in Example 2;

[0032] Figure 3 SEM image of single-crystal α-Si3N4 prepared in Example 3;

[0033] Figure 4 SEM image of the single-crystal α-Si3N4 prepared in Example 4;

[0034] Figure 5 The energy dispersive spectroscopy (EDS) characterization diagram of the single-crystal α-Si3N4 prepared in Example 4 is shown below.

[0035] Figure 6 Transmission electron microscopy image of single-crystal α-Si3N4 prepared in Example 4;

[0036] Figure 7 Selected area electron diffraction pattern of single crystal α-Si3N4 prepared in Example 4;

[0037] Figure 8 The PL spectrum of the single-crystal α-Si3N4 prepared in Example 4 is shown. Detailed Implementation

[0038] Through long-term research and extensive practice, the inventors have developed the technical solution of this invention, which will be clearly and completely described below. Obviously, the technical solution and its scope of protection of this invention include, but are not limited to, the following embodiments. The technical solution of this invention will be further explained below with reference to the embodiments.

[0039] This invention provides a method for preparing single-crystal α-Si3N4, which synthesizes single-crystal α-Si3N4 by rapidly pyrolyzing a silicon substrate coated with a boron nitride thin film using electron beam irradiation. Specifically, this invention first prepares a multi-component compound precursor, namely a silicon substrate coated with a boron nitride thin film, and then uses electron beam irradiation on the silicon substrate coated with the boron nitride thin film to prepare single-crystal α-Si3N4.

[0040] Example 1

[0041] The steps for preparing single-crystal α-Si3N4 in this embodiment are as follows:

[0042] (1) Preparation of silicon substrates coated with boron nitride thin films: Silicon wafers containing a 280nm oxide layer were immersed in piranha solution for 8 hours, then ultrasonically cleaned three times alternately with deionized water, anhydrous ethanol, and acetone, and finally purged with a nitrogen gun. The silicon substrate was placed in a magnetron sputtering chamber using an RF power supply and 99.99% pure hexagonal boron nitride as the target material, with a background vacuum of 5×10⁻⁶. -4 Under an environment of Pa, nitrogen and argon gases with a purity of 99.9999% were simultaneously turned on, with flow rates of 10 sccm and 40 sccm respectively. The gas pressure was adjusted to 1.5 Pa, and boron nitride thin films were sputtered at a power of 100 W. Amorphous thin films were obtained after approximately 3 hours of evaporation.

[0043] (2) Electron irradiation growth: A silicon substrate coated with a boron nitride film is placed in the crucible of an electron beam evaporation apparatus, with a back-bottom vacuum of 3 × 10⁻⁶. -4 Electron beam irradiation was performed under Pa conditions. The electron beam irradiation voltage was adjusted to 74 keV and the irradiation current to 15 mA. The sample was then moved onto the sample, and the high-voltage power supply current was slowly adjusted until the crucible glowed red. After irradiation for 60 seconds, the high-voltage power supply was turned off, and the crucible was allowed to cool instantly to obtain α-phase silicon nitride crystals.

[0044] Figure 1 This is a SEM image of the α-phase silicon nitride crystal prepared in this embodiment. Figure 1 It can be seen that the α-Si3N4 synthesized in this embodiment has a flower-like shape. EDS and TEM tests were performed on the α-phase silicon nitride crystal prepared in this embodiment. The results show that the interplanar spacing of the α-phase silicon nitride crystal prepared in this embodiment is 0.67 nm, and its elemental content ratio is consistent with that of single crystal α-Si3N4.

[0045] Example 2

[0046] The steps for preparing single-crystal α-Si3N4 in this embodiment are as follows:

[0047] (1) Preparation of silicon substrates coated with boron nitride thin films: Silicon wafers containing a 289 nm oxide layer were immersed in piranha solution for 9 hours, then ultrasonically cleaned three times alternately with deionized water, anhydrous ethanol, and acetone, and finally purged with a nitrogen gun. The silicon substrate was placed in a magnetron sputtering chamber using an RF power supply and 99.99% pure hexagonal boron nitride as the target material, with a background vacuum of 4 × 10⁻⁶. -4 Under an environment of 1.0 Pa, nitrogen and argon gases were simultaneously turned on, with flow rates of 20 sccm and 40 sccm respectively. The gas pressure was adjusted to 1.0 Pa, and boron nitride thin films were sputtered at a power of 160 W. Amorphous thin films were obtained after approximately 3 hours of evaporation.

[0048] (2) Electron irradiation growth: A silicon substrate coated with a boron nitride film is placed in the crucible of an electron beam evaporation apparatus, with a back-bottom vacuum of 3 × 10⁻⁶. -4 Electron beam irradiation was performed under Pa conditions. The electron beam irradiation voltage was adjusted to 85 keV and the irradiation current to 25 mA. The sample was then moved onto the sample, and the high-voltage power supply current was slowly adjusted until the crucible glowed red. After irradiation for 80 seconds, the high-voltage power supply was turned off, and the crucible was allowed to cool instantly to obtain α-phase silicon nitride crystals.

[0049] Figure 2 This is a SEM image of the α-phase silicon nitride crystal prepared in this embodiment. Figure 2 It can be seen that the α-Si3N4 synthesized in this embodiment has a pine tree-like shape. EDS and TEM tests were performed on the α-phase silicon nitride crystal prepared in this embodiment. The results show that the interplanar spacing of the α-phase silicon nitride crystal prepared in this embodiment is 0.67 nm, and its elemental content ratio is consistent with that of single crystal α-Si3N4.

[0050] Example 3

[0051] The steps for preparing single-crystal α-Si3N4 in this embodiment are as follows:

[0052] (1) Preparation of silicon substrates coated with boron nitride thin films: Silicon wafers containing a 300nm oxide layer were immersed in piranha solution for 10 hours, then ultrasonically cleaned three times alternately with deionized water, anhydrous ethanol, and acetone, and finally purged with a nitrogen gun. The silicon substrate was placed in a magnetron sputtering chamber using an RF power supply and 99.99% pure hexagonal boron nitride as the target material, with a background vacuum of 3×10⁻⁶. -4 Under an environment of 1.5 Pa, nitrogen and argon gases were simultaneously turned on, with flow rates of 40 sccm and 40 sccm respectively. The gas pressure was adjusted to 1.5 Pa, and boron nitride thin films were sputtered at a power of 140 W. Amorphous thin films were obtained after approximately 3 hours of evaporation.

[0053] (2) Electron irradiation growth: A silicon substrate coated with a boron nitride film is placed in the crucible of an electron beam evaporation apparatus, with a back-bottom vacuum of 3 × 10⁻⁶.-4 Electron beam irradiation was performed under Pa conditions. The electron beam irradiation voltage was adjusted to 80 keV and the irradiation current to 20 mA. The sample was then moved onto the sample, and the high-voltage power supply current was slowly adjusted until the crucible glowed red. After irradiation for 120 seconds, the high-voltage power supply was turned off, and the crucible was allowed to cool instantly to obtain α-phase silicon nitride crystals.

[0054] Figure 3 This is a SEM image of the α-phase silicon nitride crystal prepared in this embodiment. Figure 3 It can be seen that the α-Si3N4 synthesized in this embodiment has a fern-like shape. EDS and TEM tests were performed on the α-phase silicon nitride crystal prepared in this embodiment. The results show that the interplanar spacing of the α-phase silicon nitride crystal prepared in this embodiment is 0.67 nm, and its elemental content ratio is consistent with that of single crystal α-Si3N4.

[0055] Example 4

[0056] The steps for preparing single-crystal α-Si3N4 in this embodiment are as follows:

[0057] (1) Preparation of silicon substrates coated with boron nitride thin films: Silicon wafers containing a 300nm oxide layer were immersed in piranha solution for 12 hours, then ultrasonically cleaned three times alternately with deionized water, anhydrous ethanol, and acetone, and finally purged with a nitrogen gun. The silicon substrate was placed in a magnetron sputtering chamber using an RF power supply and 99.99% pure hexagonal boron nitride as the target material, with a background vacuum of 1×10⁻⁶. -4 Under an environment of 1.5 Pa, nitrogen and argon gases were simultaneously turned on, with flow rates of 30 sccm and 40 sccm respectively. The gas pressure was adjusted to 1.5 Pa, and boron nitride thin films were sputtered at a power of 120 W. Amorphous thin films were obtained after approximately 3 hours of evaporation.

[0058] (2) Electron irradiation growth: A silicon substrate coated with a boron nitride film is placed in the crucible of an electron beam evaporation apparatus, with a back-bottom vacuum of 3 × 10⁻⁶. -4 Electron beam irradiation was performed under Pa conditions. The electron beam irradiation voltage was adjusted to 78 keV and the irradiation current to 18 mA. The sample was then moved onto the sample, and the high-voltage power supply current was slowly adjusted until the crucible glowed red. After irradiation for 100 seconds, the high-voltage power supply was turned off, and the crucible was allowed to cool instantly to obtain α-phase silicon nitride crystals.

[0059] Figure 4 This is a SEM image of the α-phase silicon nitride crystal prepared in this embodiment. Figure 4 It can be seen that the α-Si3N4 synthesized in this embodiment has a needle-like shape. The α-phase silicon nitride crystal in this embodiment exhibits correlated emission peaks mainly at 540nm and 633nm under 325nm excitation light. Figure 8These emission peaks are related to defects in the obtained silicon nitride needle-like nanostructures. This result indicates that the morphology of the nanoneedles has a certain influence on their optical properties and has potential application value in optical fields such as photodetectors.

[0060] The α-phase silicon nitride crystal prepared in this embodiment was subjected to EDS (Electro-Degradation). Figure 5 ) and TEM Figure 6 and Figure 7 The test results showed that the interplanar spacing of the α-phase silicon nitride crystal prepared in this embodiment was 0.67 nm, and its elemental content ratio was consistent with that of single crystal α-Si3N4.

Claims

1. A method for preparing single-crystal α-Si3N4, characterized in that, It is prepared by irradiating a silicon substrate coated with a boron nitride thin film with an electron beam under vacuum conditions; The silicon substrate coated with a boron nitride thin film is prepared by the following method: (1) The silicon substrate containing the oxide layer was immersed in piranha solution for 12 to 24 hours, and then ultrasonically cleaned with deionized water, anhydrous ethanol and acetone respectively, and then blown clean with nitrogen gun to obtain the cleaned silicon substrate. (2) The cleaned silicon substrate is placed in the magnetron sputtering chamber, using an RF power supply and hexagonal boron nitride as the target material, with a back vacuum of 1 ~ 5 × 10⁻⁶. -4 In an environment of Pa, nitrogen and argon are introduced, with a flow rate ratio of nitrogen to argon of 10~40:

40. The gas pressure is adjusted to 0.6~1.5 Pa, and the power for sputtering boron nitride thin film is 100~180 W. After evaporation for 3~4 h, an amorphous thin film with a thickness of 1~3 μm is obtained.

2. The preparation method according to claim 1, characterized in that, The vacuum condition is 3 ~ 5 × 10⁻⁶. -4 Pa.

3. The preparation method according to claim 1, characterized in that, The electron beam irradiation conditions are as follows: the silicon substrate coated with boron nitride film is placed in the crucible of the electron beam evaporation equipment, and the silicon substrate coated with boron nitride film is irradiated for 10 to 120 s under the conditions of irradiation voltage of 74 ~ 85 keV and irradiation beam current of 15 ~ 25 mA. After the irradiation is completed, the high voltage power supply is turned off and the crucible is cooled instantly.

4. The preparation method according to claim 1, characterized in that, In step (1), the oxide layer thickness of the silicon substrate containing the oxide layer is 280 ~ 300 nm; the piranha solution is prepared by concentrated sulfuric acid and hydrogen peroxide, and the volume ratio of concentrated sulfuric acid to hydrogen peroxide is 7:

3.

5. The preparation method according to any one of claims 1-4, characterized in that, The single-crystal α-Si3N4 has the shape of a flower, a pine tree, a fern leaf, or a needle.

6. The preparation method according to claim 5, characterized in that, The needle-shaped single-crystal α-Si3N4 has a growth length of up to 15 μm and emission peaks at 540 nm and 633 nm under 325 nm excitation light.

7. The preparation method according to claim 6, characterized in that, The preparation conditions for the needle-shaped single crystal α-Si3N4 are as follows: a silicon substrate coated with a 2-3 μm thick boron nitride film is irradiated for 90-120 s under an irradiation voltage of 78-85 keV and an irradiation beam current of 18-25 mA.

8. Single-crystal α-Si3N4 prepared by the preparation method according to any one of claims 1-7.

9. The application of the single-crystal α-Si3N4 as described in claim 8 in micro / nano optoelectronic devices.

Citation Information

Patent Citations

  • A method to prepare a high-purity high-density monocrystalline silicon nitride nano array

    CN101550600B

  • A flowable chemical vapor deposition method for silicon nitride thin films

    CN109585264B

  • Single crystal alpha phase silicon nitride nanometer crystal whisker preparation method

    CN110357051A

  • A silicon nitride single crystal, its preparation method and application

    CN113122925B

  • A method to prepare a high-purity high-density monocrystalline silicon nitride nano array

    CN101550600A